Relação entre classes de renda e emissão de CO2 no Brasil - Bernardino, Kleber Defenti (2009)
The objectives of this study were to verify and evaluate the overall level of energy and CO2-eq emissions by class of income in Brazil, as well as changes and contributions of the brazilian energy matrix associated with these emissions between 1996 and 2003, considering the final demand of families' consumption in three classes of income separate, seeking to relate the level of CO2-eq emissions in each class of income with the corresponding efficiency and energy consumption. So are estimated the levels of CO2-eq emissions of the classes of income through the construction of the Matrix Input-Output and make the conciliation of energy data from National Energy Balance with economic data. The results show that the efficiency of carbon sector presents trend of improvement in almost all sectors. This is because Brazil has used increasingly to cleaner energy sources and consequently with lower levels of efficiency of CO2-eq. When assessing the efficiency of carbon class, it was found that even with the improvement in rates of carbon efficiency and sectoral rates of carbon in classes is a trend that the lower income classes have a level of demand for carbon emissions higher, thus a greater volume of carbon emissions for real spending than higher-income classes.